PENGARUH MODEL PEMBELAJARAN SIMAYANG UNTUK MENINGKATKAN KETERAMPILAN METAKOGNITIF PESERTA DIDIK PADA MATERI STRUKTUR ATOM - Yani Apriyani (Program Studi Pendidikan Kimia, FKIP, Universitas Muhammadiyah Cirebon, 2019)
This research was motivated by the low metacognitive skills of students and teacher-centered learning interactions. The Simayang learning model can trigger students to be more active and use their thinking skills when learning in class. The purpose of this study was to determine the improvement of students' metacognitive skills by using the Simayang learning model on atomic structure material. This research is a quasi experimental study with a quantitative approach with the design of